2010
DOI: 10.1111/j.1600-0447.2010.01636.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Assertive Community Treatment in Japan

Abstract: We concluded that ACT had a positive influence, as evidenced by a reduction of in-patient days, lower depressive symptoms, and higher client satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 5 publications
0
21
0
3
Order By: Relevance
“…For example, one study examined how assertive women managers were perceived by men and women observers, and found that although men reported positive perceptions of assertive communication in women, women reported negative perceptions of assertive women (Mathison, 1986). These studies have found that assertive community treatment, compared to the usual hospital-based rehabilitation program or placebo control, resulted in decreased depressive symptoms, higher self-reported participant satisfaction, and reduced dropout rates for adolescent inpatients with serious mental illness and adolescents in nonclinical residential care (i.e., no legal guardian; Ito et al, 2011;Jung, 2014). Recent studies conducted in Asia have focused on using assertiveness training for community well-being via assertive community treatment programs.…”
Section: Current Status Of Assertiveness Trainingmentioning
confidence: 95%
“…For example, one study examined how assertive women managers were perceived by men and women observers, and found that although men reported positive perceptions of assertive communication in women, women reported negative perceptions of assertive women (Mathison, 1986). These studies have found that assertive community treatment, compared to the usual hospital-based rehabilitation program or placebo control, resulted in decreased depressive symptoms, higher self-reported participant satisfaction, and reduced dropout rates for adolescent inpatients with serious mental illness and adolescents in nonclinical residential care (i.e., no legal guardian; Ito et al, 2011;Jung, 2014). Recent studies conducted in Asia have focused on using assertiveness training for community well-being via assertive community treatment programs.…”
Section: Current Status Of Assertiveness Trainingmentioning
confidence: 95%
“…En cuanto a la variable número de días ingresado en la UHB (ver Gráfico 3), medida que ha sido utilizada en muchos estudios de eficacia en acercamientos comunitarios como el TAC (durán, 2012;Ito et al, 2011;, se observa un descenso en la media de días ingresado significativo entre la evaluación PRE y las diferentes medidas (al año, 2 años y 3 años) (ver dibujo 6). Estos resultados convergen con otros modelos de tratamiento comunitario Bond et al, 2001), algunos de los cuales informan de reducciones de hasta un 88.15% de días ingresados en los servicios de urgencias (durán, 2012).…”
Section: Discussionunclassified
“…ACT er en effektiv form for psykososial behandling for de dårligste pasientene med schizofrenidiagnose, som ellers ville ha vaert innlagt over lang tid (446). Hvorvidt slike team også reduserer innleggelser i spesialisert psykisk helsevern, er uklart, men noen studier peker i den retningen (447).…”
Section: Act-team -Assertive Community Treatment 1aunclassified